Determinants of Excess Inventory Announcement and Stock Market Reaction in the Retail Sector - Lee,Hyun-Seok (Huck); Kesavan,Saravanan (2019)
In this paper, we empirically analyze the determinants of excess inventory announcement and the stock market reaction to the announcement in the US retail sector. We examine if the firm’s operational competence, as measured by total factor productivity (TFP), can explain the retailer’s excess inventory announcement. We also investigate if the stock market reaction to such announcements is conditional on the operational competence of the announcing firm. We use a combined dataset on excess inventory announcements, annual financial statements, and daily stock prices of publicly traded retailers in the USA between 1990 and 2011. We find that operationally competent retailers have a lower probability of announcing excess inventory in the following year. In addition, the stock market penalizes excess inventory announcements made by operationally competent retailers more severely than those made by their less competent peers. Finally, providing action information, which the firm has taken or plans to take to deal with the excess inventory, moderates the negative association between firm’s operational competence and abnormal returns due to the announcement, whereas we do not find such moderating effect with reason information.
Keywords: Supply Chain